A "three-in-one" injectable hydrogel platform with osteogenesis, angiogenesis and antibacterial for guiding bone regeneration. (September 2020) - Cheng, Ruoyu; Xin, Tianwen; Liu, Lili; Wang, Fei; Ye, Tingjun; Deng, Lianfu; Cui, Wenguo
Highlights: A general injectable hydrogel platform with enhanced osteogenesis, angiogenesis and antibacterial effect. Tunable cargoes loading capability without significant influence on the properties of hydrogel platform A multifunctional hydrogel platform with various options in loading drugs, such as hydrophilic, hydrophobic and proteins drugs. Organic-inorganic hybrid hydrogel platform in guiding bone regeneration. Abstract: Bone regeneration is a complex process consisting of three major parts, osteogenesis, angiogenesis, and antibacterial. The absence of any parts will hinder the regeneration process. For now, there are still limited researches on preparing a general platform for properly combining these three parts. Here, we proposed a strategy by using injectable 4-arm-polyethylene glycol-thiol (4-arm-PEG-SH) hydrogel incorporated with liposomes-calcium phosphate nanoparticles (Lip#CaP) to synthesized one general platform in coordinating these three parts including osteogenesis, angiogenesis and antibacterial effect (denoted as 'three-in-one' hydrogel platform). With different types and amounts of cargoes, this platform exhibited limited influence on the properties of controlled drug release, swelling, degradation, injectability and self-healing. Moreover, more than 50% inhibition effect could be observed in Escherichia coli, Staphylococcus aureus and Staphylococcus epidermis cultured with this platform. The total length and junctions' numbers of human umbilical vein endothelial cells (HUVECs) were enhanced 3- and 1.5- times by the platform in vitro . Furthermore, the alkaline phosphatase activity and extracellular matrix mineralization of MC3T3-E1 cells were increased more than 10- and 4- times by the platform in vitro . Finally, by injecting this platform to a rat calvarial critical-size defect model, after 8- weeks, significantly enhanced osteogenesis and angiogenesis were observed with the fully degradation of platform. This 'three-in-one' platform properly coordinated the osteogenesis, angiogenesis, and antibacterial effects, which could be a promising candidate to develop as a general platform for promoting bone regeneration. Graphical Abstract: Injectable 4-arm-polyethylene glycol-thiol (4-arm-PEG-SH) hydrogel incorporated with liposomes-calcium phosphate nanoparticles (Lip#CaP) to synthesized one general platform to coordinate osteogenesis, angiogenesis and antibacterial effect (denoted as 'three-in-one' hydrogel platform). Image, graphical abstract